2020
DOI: 10.1536/ihj.19-297
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Estrogen Supplementation to Autonomic and Sleep Modulations in Free-Moving Spontaneously Hypertensive Rats

Abstract: Sleep and estrogen levels have an impact on neural regulation and are associated with cardiovascular (CV) events. We investigated the effects of estrogen on heart rate variability (HRV) and circadian cycle in spontaneously hypertensive rats (SHRs). Polysomnographic recording was performed in seven male and seven female SHRs during sleep. The electroencephalogram (EEG) and electromyogram (EMG) were evaluated to define active waking (AW), quiet sleep (QS), and paradoxical sleep (PS) stages. Cardiac activities we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“… 48 Oestrogen in spontaneously hypertensive rats demonstrated improved quality of sleep in female. 49 Women with hypertension are older than those without it in our study. One possibility is that our study was participated by premenopausal and postmenopausal women, suggesting a stronger effect on insomnia due to reduced or fluctuating oestrogen levels before and after menopause.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“… 48 Oestrogen in spontaneously hypertensive rats demonstrated improved quality of sleep in female. 49 Women with hypertension are older than those without it in our study. One possibility is that our study was participated by premenopausal and postmenopausal women, suggesting a stronger effect on insomnia due to reduced or fluctuating oestrogen levels before and after menopause.…”
Section: Discussionmentioning
confidence: 46%
“…With regard to sex steroids, there is uncertainty about the effect of testosterone levels, particularly in men, on sleep disturbances; however, an association between decreased or fluctuating oestrogen levels and sleep disturbances is thought to exist in women 48. Oestrogen in spontaneously hypertensive rats demonstrated improved quality of sleep in female 49. Women with hypertension are older than those without it in our study.…”
Section: Discussionmentioning
confidence: 52%
“…Other studies have reported that high BP in the normal range was associated with PD in women, suggesting a possible influence of oestrogen and/or autonomic dysfunction 25,26 . Given that oestrogen has been implicated in www.nature.com/scientificreports/ both hypertension 27,28 and PD pathogenesis 29,30 , hormonal factors may underlie the sex-specific alteration of BP in the premotor phase of PD.…”
Section: Discussionmentioning
confidence: 99%
“…All animals were implanted in the electroencephalogram (EEG) recording electrodes on day 1 under anesthesia. The detailed surgical procedures were described in previous publications 16 18 . Under pentobarbital anesthesia (50 mg/kg, intraperitoneally), each rat was placed in a standard stereotaxic apparatus where electrodes for a parietal EEG, nuchal electromyogram (EMG), and electrocardiogram (ECG) were implanted.…”
Section: Methodsmentioning
confidence: 99%